(untitled) (Collection of scientific works «Modern structures of metal and wood», 2023)
To study the stress-strain state of the mesh dome model with the diameter 4 m, the series of glulam rods were prepared for the central compression test. The tests were carried out in the laboratory of the Department of Metal, Wooden and Plastic Structures. The stresses at the distinguished points of the elements were determined through the deformations using the resistance strain sensors. The feature of prismatic samples was the presence of stress concentrators in the support zones in the form of the holes for the location of universal connectors [3]. The significant sizes of the model made it possible to minimize the influence of the scaling factor on the obtained results. The general conclusion of the study should be considered high bearing capacity of the tested samples. The destruction of the samples took place in the support zone due to the crushing of the wood. The next tasks of the research will be the optimization of the elements sizes and testing of the dome model. The cross-section of the elements, in addition to providing the load-bearing capacity, is affected by the need to obtain certain thermotechnical characteristics of the enclosure, i.e. the elements of the dome must have the dimensions that allow placing a layer of effective insulation in their plane. A separate task is the selection of the roof, which can be considered exclusively as a part of the permanent load on the supporting system, or as a continuous shell that unfastens the frame.